Digital hygiene in education: a model for protecting students' personal data in the cloud environment - Yuliia Kovalchuk; Bilous Natalia; Наталя Білоус (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. At the moment, in the world and in Ukraine, in particular, there is an intensive digitalization of the educational process. This is accompanied by the dynamic implementation and use of cloud services (Google Workspace for Education, Microsoft 365 Education, Moodle Cloud) for the processing, storage and exchange of educational information. However, the use of such services creates significant problems for the security of students' personal data. This is due to the fact that cloud providers do not regularly provide an adequate level of access control, information privacy, and backup. The lack of clear digital hygiene among education users (students and teachers) reinforces the problem of data leakage and increases the level of cyber threats. The purpose of this work is to determine the structural components of digital hygiene during the use of cloud educational platforms and to develop a model for the protection of students' personal data, which will take into account the features of public cloud environments. The relevance of the study is explained by several global factors. In today's realities, there is a rapid increase in the use of cloud technologies in educational institutions all over the world, and, accordingly, an increase in demand for online education. Also, educational institutions are faced with the need to comply with international standards for the protection of personal data, in particular the requirements of the GDPR. Risk analysis shows that some of the most common causes of security breaches are errors in access settings (67%), phishing attacks (41%), and the use of weak passwords (34%).
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: cloud services; digital hygiene; personal data; online education